Culture-Based Education: A Literature Study in A Multi-Cultural Society - Ziraluo, Yan Piter Basman; Zebua, Nofamataro; Zebua, Ester Novi Kurnia (Journal of Humanistic, Management and Social Science Review, 2025)
This research examines the importance of local culture integration in education. The study shows that local wisdom plays an important role in shaping individual character and national progress. However, challenges such as the dominance of Western epistemology and the suppression of local knowledge hinder these efforts. This research analyses different ways to integrate local culture into the curriculum, such as including local content in textbooks and creating an inclusive learning environment. The results show that this integration can improve students' critical thinking skills, emotional intelligence and sense of national identity. The importance of meeting the needs of diverse students was also emphasised, including students from different backgrounds. Teacher training and the development of culturally relevant teaching methods are key to the successful implementation of multicultural education. In conclusion, this research highlights the importance of creating an inclusive learning environment that values cultural diversity. Thus, education can be more relevant and meaningful for all students.